Marfan’S Syndrome. A Case Presentation and Review - Loja Oropeza, David (2001)
Marfan’s syndrome is an autosomal dominant inheritance disorder that affects many body systems (skeletal, ocular, cardiovascular, cutaneous, pulmonary, abdominal, neurological). Marfan’s syndrome etiology is unknown, but recent genetic studies have linked this disorder to an extracellular microfibrillar defect located on chromosome 15q15-q21,3. Marfan’s syndrome characteristics require a multidisciplinary approach to patient care. We report a case of sporadic Marfan’s syndrome and review the clinical manifestations, the newly Ghent Criteria required for diagnosis, and management strategies, including follow-up, risk-factors modification, genetic counseling, and surgery in selected patients.